Anti-urolithiatic Activity of Andrographis Paniculata on calcium Oxalate Crystals: A preliminary in-vitro Study - Dulanjali, S.; Srikaran, R. (Journal Of Pharmaceutical Innovation, 2022)
Since centuries ago, uses of medicinal herbs to cure diseases are precious in folk and alurvedic medicinal practices. Kidney stone formation is an unbearable disease which can be found everlwhere in the world. Even in Sri Lanka the patients suffering from urolithiasis are gradually increasing. An in-vitro experimental model was prepared to evaluate the anti-urolithiatic activity of methanolic extract of Andrographispaniculataplant on pure calcium oxalate crystals. To estimate the anti-urolithiatic activity of Andrographispaniculataplant extract, the dissolution percentage ofpure calcium oxalate crystals by the plant extract was calculated and was compared with that of a standard cystonepolyherbal drug. The methanolic extract of Andrographispaniculatawas prepared by soxhlet extraction and ethanolic and aqueous extractions were prepared by soaking the powder materials for 24 hours. The titrimetric method was used to evaluate the anti-urolithiatic activity at four different concentrations such as 100 mg/L, 200 mglL,300 mg/L, and 400 mglL. Laboratory experiments were carried out on the above extract to identift the presence ofconstituent organic molecules such as alkaloids, tannin, phytosterols, terpenoids, etc. Dissolution percentage of the calcium oxalate crystals by theAndrographispaniculataplant at above concentrations were found as7l.4 (t 0.490) o/o,74.6 (t 0.2g3) o/o, g6.3 (t 0.838) o/o,and90.4(t 0.490) % respectively.5g.6 (!0.432) o/o,64.2(+ 0.163) o/o,74.8(+ 0.283) o/o, and 78.3(t 0.249) % of calcium oxalate crystals were dissolved by the standard drug at the same concentration gradient. Qualitative analysis of ethanolic and aqueous extracts of Andrographispaniculatashowed the presence of saponin, Tannin, and Terpenoids. This preliminary research revealed the enhanced dibsolution ability of calcium oxalate crystals by Andrographispaniculata plant extract. Further in-vitro and clinical studies are required to estimate the anti-urolithiatic activity of Andrographispaniculata. Subsequently, the separation of active compounds in Andrographispaniculataplant extract can lead to the discovery ofnew drugs in the future.
Keywords: Anti-urolithiatic; Methanolic; In-vitro; Andrographis paniculata